PENGARUH GAME EDUKASI “AKU JAGA DIRIKU” TERHADAP PENGETAHUAN SEKSUAL ANAK USIA 5-6 TAHUN DI TK HARAPAN BUNDA KECAMATAN TELANAIPURA - Indryani, Indryani; Rosyadi, Akhmad Fikri; Sonita, Sandra (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to determine the effect of the educational game "I take care of myself" on the sexual knowledge of children aged 5-6 years. This type of research is quantitative research using experimental methods. The design used is the Pre-Experimental Design with the form of One Group Pretest Posttest Design. The population in this study at Harapan Bunda Telanaipura Kindergarten were 40 children. The sampling technique used was purposive sampling, 14 children. The instrument used is the observation sheet. The data analysis technique used is the normality test, homogeneity test and hypothesis testing. The results of the study prove that ????ℎ???????????????????? > ???????????????????????? ie 16.125 > 2.179 at a significance level α = 0.05 this means that there is an influence from the educational game media "I significantly use" on sexual knowledge of kindergarten children 5-6 years in Harapan Bunda, Telanaipura District, namely on strong interpretation with a value of 3.17 which is in the range > 1.00 with a strong interpretation (Strong Effect). Thus the educational game media "I take care of myself" can be used in early childhood learning in schools to increase children's sexual knowledge.